Komunikasi Pembangunan Dalam Mengedukasi Masyarakat Terhadap Program Pemberian Makanan Tambahan (PMT) Untuk Mencegah Stunting Di Kelurahan Sungai Baru Kec. Banjarmasin Tengah - Amelia Puspita; Devia Hetty Hernany; Farisa Salsabila; Trinita Netiska (Departement of Mathematics Education, 2024)
This study aims to analyze the implementation of development communication in the Additional Food Program (PMT) in Sungai Baru Village as a community education effort to prevent stunting. The research employs a qualitative descriptive approach using observation, interviews, and documentation techniques. The findings show that socialization through counseling sessions at health posts and community meetings effectively increased the understanding of pregnant women and mothers of young children about the importance of balanced nutrition. Innovations such as the